2008
DOI: 10.1016/j.vaccine.2008.07.050
|View full text |Cite
|
Sign up to set email alerts
|

Gene profiling analysis of ALVAC infected human monocyte derived dendritic cells

Abstract: The recombinant canarypox virus ALVAC is being extensively studied as vaccine vector for the development of new vaccine strategies against chronic infectious diseases and cancer. However, the mechanisms by which ALVAC initiates the immune response have not been completely elucidated. In order to determine the type of innate immunity triggered by ALVAC, we characterized the gene expression profile of human monocyte derived dendritic cells (MDDCs) upon ALVAC infection. These cells are permissive to poxvirus infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
25
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 56 publications
6
25
0
2
Order By: Relevance
“…2A). This finding is consistent with several previous studies reporting that human Ad5 virus or recombinant Ad5 vector alone is generally less innate immune stimulatory and induces very little activation of DCs (30); in contrast, ALVAC vector can more potently stimulate activation of APCs, leading to expression of antiviral gene expression (15) and production of inflammatory cytokines (16). Mechanisms for limited stimulatory activity of Ad5 vector on DCs are not fully known but may be related to the fact that Ad5 virus is a human pathogen and may evolve immune escape mechanisms from innate recognition by host defense responses.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…2A). This finding is consistent with several previous studies reporting that human Ad5 virus or recombinant Ad5 vector alone is generally less innate immune stimulatory and induces very little activation of DCs (30); in contrast, ALVAC vector can more potently stimulate activation of APCs, leading to expression of antiviral gene expression (15) and production of inflammatory cytokines (16). Mechanisms for limited stimulatory activity of Ad5 vector on DCs are not fully known but may be related to the fact that Ad5 virus is a human pathogen and may evolve immune escape mechanisms from innate recognition by host defense responses.…”
Section: Discussionsupporting
confidence: 92%
“…In the context of virally vectored vaccination, such innate recognition of vector-associated PAMPs by host APCs occurs as well, but has not been well explored. Prior studies have demonstrated that ALVAC could efficiently infect human dendritic cells (DCs) (14) and induced strong antiviral response (15, 16). Similarly, human Ad5 vectors were also shown to be able to infect a range of cell types including APCs (17).…”
Section: Introductionmentioning
confidence: 99%
“…Additional PRR genes involved in innate responses to dsRNA that were down-regulated included DDX58 (also known as RIG-1 ) and thereafter IRF7 . 5, 9, 10, 52 Although DDX58 has not been previously associated with HIV infection, DDX58 is involved in antiviral innate immunity. 53, 54 We also found the transcript encoding IFIH1 , a pattern recognition receptor functioning as an IFN-induced helicase, was down-regulated.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously shown that HIV-1 infection of monocytes and DCs triggers different cellular pathways (40)(41)(42)(43)(44) and results in differential gene activation. In order to obtain a global assessment of gene expression changes induced by productive HIV-1 infection in IDCs and MDCs, microarray analyses comparing cells noninfected and infected with VSV-pseudotyped HIV-1 virus carrying Vpx were performed at the same time points (Fig.…”
Section: Resultsmentioning
confidence: 99%